2009
DOI: 10.1016/j.eneco.2008.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Market structure and the stability and volatility of electricity prices

Abstract: By using a novel approach in this paper, ;2 -analysis, we have found that electricity prices most of the time have increased in stability and decreased in volatility when the Nordic power market has expanded and the degree of competition has increased. That electricity prices at Nord Pool have been generated by a stochastic dynamic system that most often has become more stable during the step-wise integration of the Nordic power market means that this market is less sensitive to shocks after the integration pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…With the dynamic market model, the role that futures markets may play on the clearing prices and on altering the volatility and potential instability of real-time prices and generator output was examined by Watts and Alvarado [12]. Reference [13] adopted a novel approach for system controllers characterizing Nordic power market, and it was concluded that electricity prices most of the time have increased in stability and decreased in volatility when the market has expanded and the competition degree has added. In [14], an appropriate modeling of system controllers is presented to account for the effects of power system controllers on the stability of power dispatch and electricity market prices better.…”
Section: Introductionmentioning
confidence: 99%
“…With the dynamic market model, the role that futures markets may play on the clearing prices and on altering the volatility and potential instability of real-time prices and generator output was examined by Watts and Alvarado [12]. Reference [13] adopted a novel approach for system controllers characterizing Nordic power market, and it was concluded that electricity prices most of the time have increased in stability and decreased in volatility when the market has expanded and the competition degree has added. In [14], an appropriate modeling of system controllers is presented to account for the effects of power system controllers on the stability of power dispatch and electricity market prices better.…”
Section: Introductionmentioning
confidence: 99%
“…Another example of strong interconnection coupled with increasing competition is the Nordic electricity market. Bask et al (2008) [15] applied a stochastic model to generate electricity prices at Nord Pool and then used a GARCH analysis to show that prices became less sensitive to external shocks while the Nordic power market was being expanded and the degree of competition was being increased.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even though Bask and Widerberg (2009) do not focus on the market risk and the potential market risk in the Nordic power market, they utilize the aforementioned methodology when examining how the integration process at this market has affected the stability and volatility of electricity prices. Specifically, the non-parametric approach outlined above is used when estimating the stability of electricity prices, whereas four different ARCH models are used when estimating the volatility of the same prices.…”
Section: Two Variations Of ( 2 )-Analysismentioning
confidence: 99%
“…An alternative approach to monitor an asset's potential market risk, which is in the spirit of the studies in Bask and de Luna (2005) and Bask and Widerberg (2009), is the following approach: let [t {s t−p 0 +1 , s t−p 0 +2 , . .…”
Section: Two Applications Of ( 2 )-Analysismentioning
confidence: 99%